Coupling between Meshless FEM Modeling and Rendering on GPU for Real-time Physically-based Volumetric Deformation - Movania, Muhammad Mobeen (2016)
For real-time rendering of physically-based volumetric deformation, a meshless finite element method (FEM) is proposed and implemented on the new-generation Graphics Processing Unit (GPU). A tightly coupled deformation and rendering pipeline is defined for seamless modeling and rendering: First, the meshless FEM model exploits the vertex shader stage and the transform feedback mechanism of the modern GPU; and secondly, the hardware-based projected tetrahedra (HAPT) algorithm is used for the volume rendering on the GPU. A remarkable feature of the new algorithm is that CPU readback is avoided in the entire deformation modeling and rendering pipeline. Convincing experimental results are presented.